2022
DOI: 10.1172/jci.insight.157203
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IRE1 endoribonuclease activity alleviates cardiovascular lesions in a murine model of Kawasaki disease vasculitis

Abstract: Kawasaki disease (KD) is the leading cause of non-congenital heart disease in children. Studies in mice andhumans propound the NLRP3-IL-1β pathway as the principal driver of KD pathophysiology. Endoplasmic reticulum (ER) stress can activate the NLRP3 inflammasome, but the potential implication of ER stress in KD pathophysiology has not been investigated. We used human patient data and the Lactobacillus casei cell wall extract (LCWE) murine model of KD vasculitis to characterize the impact of ER stress on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
(134 reference statements)
1
7
0
Order By: Relevance
“…Taken together, the results have demonstrated that three ER stress pathways, ATF6, PERK, and IRE1, participate in the pathogenesis of human aortic aneurysms and mouse Ang II abdominal aortic and thoracic aneurysms. Our findings are well correlated with previous reports in patients with AAA ( 26 ), and AAA mouse models, including VSMC-specific IRE1 downstream transcription factor X-box binding protein 1 (XBP1) ( 58 )-KO mice ( 27 ), myeloid-specific IRE1-KO mice ( 28 ), VSMC-specific gasdermin D (GSDMD)-KO mice ( 59 ), and elastase-induced AAA treated with a PERK inhibitor ( 29 ) ( Figure 4I ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, the results have demonstrated that three ER stress pathways, ATF6, PERK, and IRE1, participate in the pathogenesis of human aortic aneurysms and mouse Ang II abdominal aortic and thoracic aneurysms. Our findings are well correlated with previous reports in patients with AAA ( 26 ), and AAA mouse models, including VSMC-specific IRE1 downstream transcription factor X-box binding protein 1 (XBP1) ( 58 )-KO mice ( 27 ), myeloid-specific IRE1-KO mice ( 28 ), VSMC-specific gasdermin D (GSDMD)-KO mice ( 59 ), and elastase-induced AAA treated with a PERK inhibitor ( 29 ) ( Figure 4I ).…”
Section: Resultssupporting
confidence: 91%
“…Although some downstream regulators of ER stress, including XBP1 ( 27 ), IRE1 ( 28 ), or PERK ( 29 ), have been identified as potential targets for AAA, the detailed molecular mechanisms of experimentally verified ER stress genes in specific areas of the aorta (abdominal or thoracic aorta) are poorly documented. We hypothesized that ER stress-induced genes partially overlapped with upregulated genes in Ang II abdominal AA and thoracic AA.…”
Section: Resultsmentioning
confidence: 99%
“…Our study is not the first to demonstrate that Ire1a downregulation can decrease UPR-mediated cell death. Inhibiting Ire1a activity in a mouse model of Kawasaki disease vasculitis was sufficient to decrease cell death [40]. Furthermore, in a human acute myeloid leukemia study, patients that had defective CEBPA double mutants had increased Ire1a expression [41].…”
Section: Discussionmentioning
confidence: 96%
“…Overall, their findings show that pharmacological or genetic suppression of IRE1 signaling in macrophages lowers NLRP3 inflammasome activation and mRNA expression of inflammatory cytokine caused by LCWE. In addition, LCWE‐injected LysM Cre+ Ern1 Δ/Δ animals had lower blood IL‐1β levels and caspase‐1 activity compared to their Ern1 fl/fl littermate control counterparts (Marek‐Iannucci et al, 2022).…”
Section: Nlrp3 and Kdmentioning
confidence: 98%
“…Also, it has been shown that stimulation of macrophages with saturated fatty acid leads to activation of NLRP3 and IL‐1β due to RNase activity of IRE1 (Robblee et al, 2016; Tufanli et al, 2017). Owing to these associations between IRE1 activity during ER stress and NLRP3 activation, Marek‐Iannucci et al (2022) hypothesized that IRE1 activation might play a role in the pathogenesis of KD. They showed, using single‐cell RNA sequencing (scRNA‐seq) study of abdominal aortas and spatial transcriptomics of heart tissues, that myeloid cells infiltrating the cardiovascular lesions of LCWE‐injected animals coexpress NLRP3, PYCARD, caspase1, and IL‐1β and are probably the source of IL‐1β.…”
Section: Nlrp3 and Kdmentioning
confidence: 99%